2012
DOI: 10.1179/1743132812y.0000000080
|View full text |Cite
|
Sign up to set email alerts
|

The involvement of nitric oxide in the anti-seizure effect of acute atorvastatin treatment in mice

Abstract: In conclusion, anti-convulsant effect of atorvastatin was demonstrated in two seizure models of electroshock and intraperitoneal pentylenetetrazole. Nitric oxide release, probably through inducible nitric oxide synthase at least in part is responsible for this effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 46 publications
0
18
1
Order By: Relevance
“…However, there are some studies which have reported non-effect or even protective effects for iNOS activation in seizure susceptibility [25,29,59]. In contrast to our data, some investigators showed iNOS inhibition (by aminoguanidine) reversed the anticonvulsant effects of acute or chronic atorvastatine treatment in different seizure paradigms [59,60]. This difference could be due to the variation in type of seizure, source of NO, and other neurotransmitter systems involved in seizure susceptibility [61].…”
Section: Discussioncontrasting
confidence: 84%
“…However, there are some studies which have reported non-effect or even protective effects for iNOS activation in seizure susceptibility [25,29,59]. In contrast to our data, some investigators showed iNOS inhibition (by aminoguanidine) reversed the anticonvulsant effects of acute or chronic atorvastatine treatment in different seizure paradigms [59,60]. This difference could be due to the variation in type of seizure, source of NO, and other neurotransmitter systems involved in seizure susceptibility [61].…”
Section: Discussioncontrasting
confidence: 84%
“…In recent years, statins have been found to have neuroprotective effects in stroke 6 and are recommended as neuroprotective agents in acute stroke treatment. [8][9][10][11][12] However, no study has been conducted to investigate the effect of statins on the risk of poststroke seizures, even though statins are used widely in stroke patients. [8][9][10][11][12] However, no study has been conducted to investigate the effect of statins on the risk of poststroke seizures, even though statins are used widely in stroke patients.…”
mentioning
confidence: 99%
“…In addition to reducing the serum cholesterol levels, statins have various pleiotropic effects such as increasing nitric oxide (NO), reducing oxidative stress, neuroinflammation, and neurotoxicity. 3 Increasing evidence indicates that statins are neuroprotective in various conditions, including stroke, cerebral ischemia and traumatic brain injury. 3 As statins possess antioxidant, neuroprotective effects, they may be expected to possess antiepileptic activity too.…”
Section: Introductionmentioning
confidence: 99%
“…3 Increasing evidence indicates that statins are neuroprotective in various conditions, including stroke, cerebral ischemia and traumatic brain injury. 3 As statins possess antioxidant, neuroprotective effects, they may be expected to possess antiepileptic activity too. However, only scanty reports are available on anticonvulsant action of statins and in them some comprise controversial reports of atorvastatin on experimental seizure models.…”
Section: Introductionmentioning
confidence: 99%